Friendship at work and error disclosure - Hsiao-Yen Mao; An Tien Hsieh (BRQ Business Research Quarterly, 2017)
Organizations rely on contextual factors to promote employee disclosure of self-made errors, which induces a resource dilemma (i.e., disclosure entails costing one's own resources to bring others resources) and a friendship dilemma (i.e., disclosure is seemingly easier through friendship, yet the cost of friendship is embedded). This study proposes that friendship at work enhances error disclosure and uses conservation of resources theory as underlying explanation. A three-wave survey collected data from 274 full-time employees with a variety of occupational backgrounds. Empirical results indicated that friendship enhanced error disclosure partially through relational mechanisms of employees' attitudes toward coworkers (i.e., employee engagement) and of coworkers' attitudes toward employees (i.e., perceived social worth). Such effects hold when controlling for established predictors of error disclosure. This study expands extant perspectives on employee error and the theoretical lenses used to explain the influence of friendship at work. We propose that, while promoting error disclosure through both contextual and relational approaches, organizations should be vigilant about potential incongruence."
Keywords: 650; Friendship at work; Error disclosure; Employee engagement; Perceived social worth